SOCIOLOGICAL STUDY OF SOCIAL, ECONOMIC PROBLEMS AND DYNAMICS OF “BARELA” TRIBE - Bajpai, Suyash Sagar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
According to the census of 2011, the total population of the state is 7,26,26,809. Out of which 1,53,16,784 population is of scheduled tribe i.e. 21.60% population of the state is tribal. In terms of population of scheduled tribe, Alirajpur is at first place in Madhya Pradesh. A total of ‘47’ tribes and sub-tribes are found in Madhya Pradesh. Tribal development blocks are ‘89’.